2020
DOI: 10.1155/2020/8980124
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 Drives Stimulations of Timosaponin AIII‐Induced Anticancer Effects in Human Osteosarcoma Cells

Abstract: A ginsenoside Rg1 is an active compound extracted from the stem and/or root of ginseng. Rg1 has been known to affect various human organ systems including the immune, cardiovascular, and nervous systems with its pharmacological effects. Timosaponin AIII (TA3) is a type of spirostanol saponins that are the major compounds of Anemarrhena asphodeloides. TA3 exerts anticancer effects in various human cancers, and the effects include attenuations of cancer cell migration and induction of apoptosis. In this study, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…Even though there are numerous molecules proposed to be targets for suppressing metastatic abilities of cancers and inflammatory diseases, MMPs are one of the most intriguing ones because both their ECM degradation and non-enzymatic modes of action considerably contribute to metastasis and immune responses. Since ginsenosides’ MMP suppression had synergy with a few known compounds, co-treatment with other chemicals including MMP inhibitors may also exhibit promising results in the future [ 67 , 85 , 108 , 128 ]. This escalates the value of ginsenosides as promising anti-cancer and anti-inflammatory agents to be further developed and modified.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though there are numerous molecules proposed to be targets for suppressing metastatic abilities of cancers and inflammatory diseases, MMPs are one of the most intriguing ones because both their ECM degradation and non-enzymatic modes of action considerably contribute to metastasis and immune responses. Since ginsenosides’ MMP suppression had synergy with a few known compounds, co-treatment with other chemicals including MMP inhibitors may also exhibit promising results in the future [ 67 , 85 , 108 , 128 ]. This escalates the value of ginsenosides as promising anti-cancer and anti-inflammatory agents to be further developed and modified.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rg1 can exert synergistic MMP-inhibiting effects with other drugs. A recent study showed that Rg1 could intensify anti-metastatic effects of Timosaponin AIII, an anti-cancer steroid saponin, in MG63 and U2OS osteosarcoma cells [ 67 ]. In particular, gelatin cleavage by MMP-2 and MMP-9 were remarkably reduced via transcriptional regulation when cells were exposed to both Timosaponin AIII and Rg1.…”
Section: Anti-metastatic and Anti-inflammatory Effects Of Ginsenosmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginseng, the root of Panax ginseng C. A. Meyer, has been used for thousands of years as a traditional Chinese medicine (TCM) in Asian countries to strengthen immunity, supply nutrition, and decrease fatigue. Ginsenosides are the major active components in ginseng, having a variety of bioactive and pharmacological activities, including anticancer, 1,2 antitumor, 3,4 antidiabetic, 5,6 antihypertensive, 7 antifatigue, 8 and antiaging effects 9 . More than 500 kinds of ginsenosides have been identified from ginseng and related herbs 10,11 .…”
Section: Introductionmentioning
confidence: 99%